UJI EFEKTIVITAS DOSIS PHOSFOR TERHADAP PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS TANAMAN PADI (Oryza sativa L.) - Narju, Mula; Hamzani, Ikhlas; Hafnizar, Aira; Effendi, Usman (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
Rice (Oryza sativa L.) is an important food source in Indonesia, facing challenges such as population growth and declining land productivity. This research was conducted in the rice fields of Kulam Jeureuneh village, Beutong District, Nagan Raya Regency, Aceh Province, from July to October 2024. The method used was a Factorial Randomized Block Design (RBBD) with two factors: phosphorus doses (27 kg, 36 kg, and 45 kg P2O5/ha) and three rice varieties (Ciherang, Mekongga, and Inpari 20). The results showed that phosphorus did not significantly affect vegetative growth due to fixation in the soil, while the differences between varieties had a significant effect on growth and yield, with Inpari 20 demonstrating superior adaptability and productivity. Therefore, it is recommended that farmers understand which varieties have good adaptation to the environment to enhance their land productivity. Additionally, appropriate fertilization recommendations can strengthen the obtained results. Further research on specific fertilization methods, such as the use of organic fertilizers or microbe-based fertilization, is highly recommended for implementation.